1980
DOI: 10.1128/iai.27.2.690-692.1980
|View full text |Cite
|
Sign up to set email alerts
|

New type of antibody-enzyme conjugate which specifically kills Candida albicans

Abstract: A new type of antibody-enzyme conjugate was made, and its possible application to Candida infection was studied. Both lactoperoxidase and xanthine oxidase were conjugated to specific antibody against Candida albicans. In vitro microbiocidal activity of the new antibody-enzyme conjugate, when incubated together with xanthine and a minute amount of halides, showed a remarkable level of candidacidal ability. When the new antibody-enzyme conjugate was given to Candida-infected mice, followed by injecting xanthine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Okuda et al (8) have suggested that lactoperoxidase might be useful for the treatment of cancer and infectious disease by complexing the enzyme with antibody specific for the desired target. Using a murine model of renal candidiasis, they demonstrated a significant therapeutic effect of lactoperoxidase conjugated to anti-Candida antibody.…”
mentioning
confidence: 99%
“…Okuda et al (8) have suggested that lactoperoxidase might be useful for the treatment of cancer and infectious disease by complexing the enzyme with antibody specific for the desired target. Using a murine model of renal candidiasis, they demonstrated a significant therapeutic effect of lactoperoxidase conjugated to anti-Candida antibody.…”
mentioning
confidence: 99%